Elastic and aeroelastic behavior of electromechanical coupled structures in cases of energy harvesting and structural control considering piezoelectric nonlinearities. - Dias, José Augusto de Carvalho (2019)
Several research groups have extensively investigated smart materials over the last decades. Applications range from sensing and actuation, the combination of both in vibrations control and more recently, in energy harvesting problems. Among the different smart materials available, piezoelectric one has received great attention in the literature. They can be employed over a large and useful range of frequencies and different configurations are commercially available. Among different applications, aeronautical engineering has benefited from the researches related to smart materials. In particular, these materials have provided advances in the development of bio-inspired structures, control of structural properties in order to improve the aeroelastic performance as well as in wind energy harvesting. Linear constitutive equation of piezoelectricity has been considered in most cases for the modeling of such systems. However, recent literature shows that nonlinear manifestations of piezoelectric materials are relevant and can significantly modify the behavior of an electromechanically coupled system both in actuation or sensing problems. In this work, a nonlinear plate finite element model has been developed in order to obtain the governing equations of electromechanically coupled systems. The model also considers the nonlinear behavior piezoelectric material under weak electric fields. The nonlinear electroelastic model results are verified against experimental data in actuation and vibration based energy harvesting cases. Later, the nonlinear structural model is combined to an unsteady aerodynamic model. The effects of nonlinear piezoelectricity are investigated considering an electromechanically coupled flexible wing. The active stiffness change induced by piezoelectric actuation is also investigated as an aeroelastic control technique.